Design and Technical Analysis of Rooftop and Ground-Mounted Photovoltaic System Implementation in an Industrial Area: A Case Study of PT X - Dewangga, Bagas Wahyu (Master in Systems Engineering, 2026)
This research presents a comprehensive technical assessment of grid-connected rooftop and ground-mounted photovoltaic (PV) systems implemented in an industrial zone at PT. X, Gresik, East Java. The study incorporates site-specific analysis of available rooftop and open land areas, solar irradiation characteristics, and environmental parameters, including ambient temperature and wind speed. System performance was simulated using PVSyst version 8.0 based on primary field data and meteorological databases.Two PV system configurations were developed and analyzed. Scenario 1 utilized 450 Wp monocrystalline modules with 25 kW on-grid inverters, resulting in a total installed capacity of 510.30 kWp and an estimated annual energy production of 755.02 MWh. Scenario 2 employed 455 Wp monocrystalline modules with 33 kW grid-tied inverters, yielding an installed capacity of 492.62 kWp and an annual energy output of 711.77 MWh. The results indicate that ground-mounted systems on vacant land provide higher energy yields due to optimized module orientation and reduced shading losses, while rooftop systems offer substantial complementary contributions. Overall, the study confirms the technical feasibility and effectiveness of integrating large-scale PV systems in industrial areas to support energy efficiency and emission reduction targets.